Team Communication During Patient Handover From the Operating Room: More Than Facts and Figures. (February 2013) - Manser, Tanja; Foster, Simon; Flin, Rhona; Patey, Rona
Objective: This study was aimed at examining team communication during postoperative handover and its relationship to clinicians' self-ratings of handover quality. Background: Adverse events can often be traced back to inadequate communication during patient handover. Research and improvement efforts have mostly focused on the information transfer function of patient handover. However, the specific mechanisms between handover communication processes among teams of transferring and receiving clinicians and handover quality are poorly understood. Method: We conducted a prospective, cross-sectional observation study using a taxonomy for handover behaviors developed on the basis of established approaches for analyzing teamwork in health care. Immediately after the observation, transferring and receiving clinicians rated the quality of the handover using a structured tool for handover quality assessment. Handover communication during 117 handovers in three postoperative settings and its relationship to clinicians' self-ratings of handover quality were analyzed with the use of correlation analyses and analyses of variance. Results: We identified significantly different patterns of handover communication between clinical settings and across handover roles. Assessments provided during handover were related to higher ratings of handover quality overall and to all four dimensions of handover quality identified in this study. If assessment was lacking, we observed compensatory information seeking by the receiving team. Conclusion: Handover quality is more than the correct, complete transmission of patient information. Assessments, including predictions or anticipated problems, are critical to the quality of postoperative handover. Application: The identification of communication behaviors related to high-quality handovers is necessary to effectively support the design and evaluation of handover improvement efforts.